A Multi-Systems Approach to Human Movement after ACL Reconstruction: The Nervous System - Meredith Chaput; Brandon M Ness; Kathryn Lucas; Kory J Zimney (International Journal of Sports Physical Therapy)
Postoperative rehabilitation of anterior cruciate ligament (ACL) reconstruction mainly focuses on the restoration of strength and range of motion with a long-term goal to return athletes to their prior level of activity. Of those wanting to return to sport, many are either unable and/or experience protracted recovery despite extensive rehabilitation. To holistically care for patients recovering from ACL reconstructions, reframing rehabilitation to consider a comprehensive systems approach (including musculoskeletal, cardiovascular, endocrine, and neurologic systems) may help improve treatment outcomes. The American Physical Therapy Association has adopted a vision statement that embraces the concept of a ‘movement system,’ but validation of the movement system has been challenging. Application of a multi-physiologic systems approach may provide a unique perspective to better understand the nervous system and its interactions after ACL reconstruction. The purpose is to focus on the nervous system contributions to a multi-physiologic system approach to rehabilitation from ACL reconstruction.